Detección de Salmonella sp. en heces de palomas como trasmisor de infecciones en muestras obtenidas de plazas y parques de Riobamba - Oscar Efraín, Bagua Paguay (2020)
Salmonella sp. It is a gram-negative bacterium that causes enteric diseases, they are housed in the viscera, skin, and birds’ feces such as pigeons, these, when deposited on outdoor surfaces become a health risk, since they can contaminate the environment with various microorganisms through the wind. The research aimed to determine Salmonella sp. in pigeon feces as a transmitter of infections in samples obtained from squares and parks in the city of Riobamba, to do this, some microbiological study methods were used. The research was descriptive, with a mixed approach, cross-sectional type, and non-experimental methodological design. Random sampling was applied at the study sites, 50 samples were collecting and analyzed by microbiological techniques using sources such as Tetrationate, MacConkey agar, Salmonella-Shigela agar, Müller-Hinton agar, physiological tests, biochemical tests and the Kirby-Bauer method, obtaining negative results for Salmonella sp. in the samples analyzed, at the same time we identify 7 types of gram-negative bacteria such as Citrobacter diversus, Citrobacter amalonaticus, Citrobacter freundii, Proteus mirabilis, Proteus vulgaris, Enterobacter cloacae and Escherichia coli. In the antibiogram a resistance mechanism towards Quinolones by the bacteria Proteus mirabilis were observed. These results prove that despite the absence of Salmonella sp. in fecal samples of pigeons, these birds act as reservoirs of various pathogenic microorganisms that can affect human health if sanitary or hygiene measures are not practiced